Daily walking is effective for the management of pregnant women with gestational diabetes mellitus. Issue 9 (5th July 2018) - Hayashi, Ayako; Oguchi, Hidenori; Kozawa, Yumi; Ban, Yukiko; Shinoda, Junji; Suganuma, Nobuhiko
Abstract: Aim: This study evaluated the usefulness of daily walking for gestational diabetes mellitus (GDM) management by analyzing the relationship between daily walking and glucose tolerance in pregnant women with GDM who were in the second trimester. Methods: This longitudinal study was conducted at TOYOTA Memorial Hospital in Toyota, Japan, from January 2015 to June 2016. Pregnant women with GDM wore accelerometers on the waist for 7–12 weeks. Results: Seventy‐three women with GDM were included in the present study; data collected from 24 women were analyzed. The estimated number of steps walked daily showed a significant positive correlation ( r = 0.798, P = 0.000) with energy expenditure related to physical activity. There was a significant negative correlation ( r = −0.603, P = 0.014) between the post‐ to pre‐research casual glucose level (CGL) ratio and the number of steps walked daily. No significant correlation ( r = −0.004, P = 0.986) was detected between the ratio of hemoglobin A1c and the number of steps taken. When the study was completed, the 11 participants who walked ≥6000 steps/day showed significantly lower CGL (95 + 10 mg/dL [mean + SD]) than the 13 participants in the <6000 steps/day group (111 + 18 mg/dL) ( P = 0.013). Conclusion: Simple walking for light intensity physical activity is effective for controlling the CGL in pregnant women with GDM. We recommend that pregnant women with GDM should walk a minimum of 6000 steps/day.